Exploring antimycobacterial potential and profiling secondary metabolite gene clusters in the whole genome of Bacillus isolated from dogfruit (Archidendron pauciflorum) - Jepri Agung Priyanto, Muhammad Eka Prastya, Egiyanti Nur Widhia Hening, Rika Indri Astuti (Journal of Applied Pharmaceutical Science, 2025)
Bacillus spp. associated with tropical medicinal plants are potential sources of secondary metabolites possessing antimycobacterial properties. This study evaluated the antimycobacterial activity of endophytic Bacillus species against Mycobacterium smegmatis and analyzed putative secondary metabolite gene clusters (SMGCs) in the complete genome sequence of the selected isolate. Among the four isolates tested, colony and metabolite extract from Bacillus sp. strain DJ4 strongly inhibited the growth of M. smegmatis, a surrogate bacterium for Mycobacterium tuberculosis (Mtb). The extract was categorized as bactericidal, since the minimum inhibitory concentration (MIC) and MBC of the bacterial extract were 31.25 μg/ml and 125 μg/ml, respectively. The most effective inhibition of biofilm formation and eradication of M. smegmatis cells’ biofilm was shown by the 2 × MIC extract treatment. Eighteen volatile compounds (VOCs) were identified by gas chromatography-mass spectrometry analysis. Some VOCs found in the extract have been reported to act as antibacterial agents. Whole-genome analysis revealed that Bacillus sp. strain DJ4 is similar to Bacillus velezensis strain KCTC 13012. Eight SMGCs were identified in the bacterial genomes. In conclusion, the present study indicates that endophytic Bacillus species, especially Bacillus sp. strain DJ4, are a new source of antimycobacterial compounds. This discovery may allow further exploration of secondary metabolites and genomic features of this endophytic bacterium to open up great prospects in the pharmaceutical industry to combat Mtb infection.
Keywords: Endophyte, Bacillus, Biofilm, Genome, Mycobacterium smegmatis, Secondary metabolite gene cluster